Start-up Exits: Evidence from the Czech Republic - Vejmělková, Lada (University of Dubrovnik, 2024)
The aim of this paper is to identify the main characteristics of start-up exits in the Czech Republic. The research gap stems from the lack of research on the start-up exits. For this purpose, the unique Czech Founders database has been used, which includes data on 100 transactions for the 2007-2021 period. Data are evaluated using selected statistics methods. The results indicate that there are statistically significant differences between the industry and the location of the start-up. This research is the first ever to map start-up exits in the Czech context. The contribution of extending the current state of knowledge is the formulation and application of tools supporting the development of entrepreneurial ecosystems by policy makers.

The aim of this paper is to identify the main characteristics of start-up exits in the Czech Republic. The research gap stems from the lack of research on the start-up exits. For this purpose, the unique Czech Founders database has been used, which includes data on 100 transactions for the 2007-2021 period. Data are evaluated using selected statistics methods. The results indicate that there are statistically significant differences between the industry and the location of the start-up. This research is the first ever to map start-up exits in the Czech context. The contribution of extending the current state of knowledge is the formulation and application of tools supporting the development of entrepreneurial ecosystems by policy makers.
Start-up Exits: Evidence from the Czech Republic
Keywords: start-up; business angel; venture capital; exit; exit strategy; Czech republic; start-up; business angel; venture capital; exit; exit strategy; Czech republic